Teaching English Grammar through Genre-Based Approach for Students at a History of Islamic Civilization Department - Saehu, Andang; Hanifah, Anisa (English Teaching and Linguistics Journal (ETLiJ), 2024)
English learning for foreign learners continues to be necessary even formally up to the university level. One of the attempts to actualize this is by requiring undergraduate students to take English language learning courses at any degree. On the other side, teaching English has many approaches and methods, among the approaches to teaching English is the Genre-Based Approach. Therefore, this research aims to describe how was a Genre-Based Approach implemented in teaching English Grammar course for first-year students at the History of Islamic Civilization department, at the State Islamic University of Sunan Gunung Djati Bandung. This research indicates that integrating Genre-Based Approach into teaching English Grammar course enhances students' comprehension and production of grammatical structures within authentic communicative contexts. This research uses qualitative methods and observation techniques in collecting and analyzing the effectiveness of the Genre-Based Approach in teaching English Grammar. The results of the implementation of this genre-based approach showed a significant improvement in the writing ability of students of the history of Islamic civilization. Therefore, teaching English grammar through a genre-based approach opens up the way for the development of meaningful and relevant writing skills for history of Islamic civilization students, preparing them to communicate effectively in academic and professional contexts.